Orthodontic movement of teeth with intraosseous defects: histologic and histometric study in dogs - Cirelli, C. C.; Cirelli, Joni Augusto [UNESP]; Martins, JCD; Lia, Raphael Carlos Comelli [UNESP]; Rossa, C.; Marcantonio, E. (Mosby, Inc, 2003)
The purpose of this study was to evaluate histologically, in dogs, the periodontal healing of 1-walled intraosseous defects in teeth that were subjected to orthodontic movement toward the defects. The defects were surgically created bilaterally at the mesial aspects of the maxillary second premolars and distal aspects of the mandibular second premolars of 4 mongrel dogs. One week after creating the defects, an orthodontic appliance was installed, and the teeth were randomly assigned to 1 of 2 treatment groups: those in the test group received a titanium-molybdenum alloy rectangular wire spring that performed a controlled tipping root movement, and those in the control group received a passive stainless steel wire. Active orthodontic movement of the test teeth lasted 2 months and was followed by a stabilization period of another 2 months, after which the animals were killed. Throughout the study, routine daily plaque control was performed on the dogs with a topical application of a 2% chlorhexicline gel. The results showed no difference between the groups, with some regularization of the defects and periodontal regeneration limited to the apical portion of the defects. Histometric analysis showed a significant difference in bone height; on average, it was 0.53 mm smaller in the test group. It was concluded that orthodontic movement does not interfere with the healing of 1-walled intraosseous defects, with the exception of the linear extent of new bone apposition.